It’s Double Edged: The Positive and Negative Relationships Between the Development of Moral Reasoning and Video Game Play Among Adolescents - Hodge, Sarah E.; Taylor, Jacqui; McAlaney, John (Frontiers in Psychology, 2019)
Due to the concerns over the effects of video game play, this study investigated adolescents’ moral development and their video game play. 166 adolescents aged 11-18 years (M = 13.08 SD = 1.91) attending an English school completed an online survey, which included a measure of moral development and questions regarding video game play. In contrast to previous research, male participants were found to have significantly (p = 0.02) higher moral reasoning scores than females. The results also suggested a transition in moral development, which takes place between the ages of 12–14. The results of moral development and video game played suggested both positive and negative relationships. Regression analysis suggested that there was a significant positive relationship between the more types of game genres played and higher moral scores. Although not significant, the results suggested trend for the following variables; years playing video games, mature content, engagement, moral narrative, Grand Theft Auto, Call of Duty, and length of time playing video games had a negative relationship with moral scores. The implications of these results are discussed with regards to moral education and the variables involved in video game play including the role content of video games.